1991
DOI: 10.1111/j.1600-0447.1991.tb03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence of specific mental disorders among people born in Iceland in 1931

Abstract: The lifetime prevalence rates are presented for mental disorders in a random sample of people born in Iceland in 1931, interviewed at the age of 55–57 years. The diagnoses are made according to DSM‐III, on the basis of the National Institute of Mental Health's diagnostic Interview Schedule (NIMH‐DIS) used by trained lay interviewers. The most common diagnoses were alcohol abuse and dependence, generalized anxiety disorder, phobic disorders, dysthymic disorder and major depressive episode. Disorders more common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 15 publications
5
44
0
Order By: Relevance
“…Differences may also be due Substance use, mood and anxiety disorders BF Grant et al to diagnostic criteria used in the current study (that is, DSM-IV) and prior studies that used earlier DSM classifications or ICD-10 criteria. Consistent with most prior cross-sectional 27,[50][51][52][53][54][65][66][67][68][69][70][71] and longitudinal research, 2,11-14 incidence rates of MDD and anxiety disorders except social phobia were greater among women, whereas incidence rates of most substance use disorders were greater among men. Also consistent with these prevalence surveys, there were no sex differences in the incidence of bipolar I and II disorders.…”
Section: Discussionsupporting
confidence: 76%
“…Differences may also be due Substance use, mood and anxiety disorders BF Grant et al to diagnostic criteria used in the current study (that is, DSM-IV) and prior studies that used earlier DSM classifications or ICD-10 criteria. Consistent with most prior cross-sectional 27,[50][51][52][53][54][65][66][67][68][69][70][71] and longitudinal research, 2,11-14 incidence rates of MDD and anxiety disorders except social phobia were greater among women, whereas incidence rates of most substance use disorders were greater among men. Also consistent with these prevalence surveys, there were no sex differences in the incidence of bipolar I and II disorders.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore he found that the expectancy of becoming psychotic before the age of 61 was between 4% and 5%. Stefansson et al 13 using the diagnostic interview schedule, carried out a study of a cohort consisting of half of all Icelanders born in 1931. They found the lifetime prevalence of psychotic and major depressive disorders (using the DSM-III classification) to be about 6% in the cohort at the age of 57.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence data were highly sensitive to elements of study design and methodology. Consistent with existing literature, prevalence in females was higher than in males (107,137,138) and 12-month prevalence was higher than point prevalence (139)(140)(141).…”
Section: Discussionsupporting
confidence: 80%